Comparison of early F-18 Florbetaben PET/CT to Tc-99m ECD SPECT using voxel, regional, and network analysis - Soo Jin Kwon (Nature Portfolio, 2021)
Abstract This study aimed to validate early-phase F-18 Florbetaben positron emission tomography (eFBB PET) as a brain perfusion test and determine the optimal reference region. A total of 27 patients with early Parkinson’s disease with Tc-99m ethyl cysteinate dimer single photon emission tomography (ECD SPECT) and FBB PET were included. Six reference regions, including whole brain (GN), pons, central white matter (CWM), whole cerebellum (WC), WC with brain stem (WC + B), and cerebellar grey matter (CG), were applied to obtain SUVR using cortex volume-of-interest (VOI). Reference regions of WC (r 0.886), WC + B (r 0.897), and CG (r 0.904) had highest correlation values of cortex-VOI SUVR between both perfusion images (all p < 0.001). Early-phase FBB PET had a significant linear correlation of CG-normalized SUVR of the cortex, basal ganglia, thalamus, and midbrain with ECD SPECT in voxel-wise analysis (FDR adjusted-p < 0.05). Early-phase FBB PET extracts more ICNS than ECD SPECT, as 9 ICNS and 4 ICNs, respectively. Both eFBB PET and ECD SPECT well discriminated PD from DLB (Area-under-curve of receiver-operating-characteristics, 0.911 for eFBB PET, 0.922 for ECD SPECT). Our findings suggest that eFBB PET is a reliable perfusion test based on a high correlation with ECD SPECT using cerebellum-based normalization methods.